TINJAUAN PERUBAHAN KEBIJAKAN PELAYANAN PUBLIK BERBASIS HAK ASASI MANUSIA DI INDONESIA - Awaludin Al-Azhar, Afif; Suratman, Suratman; Yogopriyatno, Jatmiko; Sartika, Sartika (PESIRAH: Jurnal Administrasi Publik, 2023)
There have been changes in human rights-based public service policy as efforts to advance human rights and improve service quality in Indonesia. Therefore, this study aims to identify existing changes, factors driving policy changes, policy implementation in the field, and challenges arising in policy implementation. The research method used is descriptive qualitative, with data collected from observations, interviews, and documentation. The results show changes in human rights-based public service policy, including the addition of definitions, human rights principles, scope, stages of forming P2HAM, P2HAM criteria, involvement of academics and civil society in assessments, and no longer focusing on the term 'appreciation' but using the term 'P2HAM Work Unit'. Factors driving public policy changes include the government's responsibility in enforcing human rights, evaluation of existing regulations, and the need for terminological changes. Moreover, the implementation of human rights-based public services in the field is not optimal due to challenges such as inadequate resource availability, absence of sanction regulations, lack of work programs and budget plans, and deviant practices in public service provision. Based on the research results, practical or managerial implications emphasize the importance of adaptation and innovation in policy and operational management to enhance the quality and effectiveness of human rights-based public services.